What goes around comes around: The fate of stars in stripped tails of gas - Akerman, N.; Tonnesen, S.; Poggianti, B.; Smith, R.; Werle, A.; Giunchi, E.; Vulcani, B.; Fritz, J. (Astronomy and astrophysics (Berlin), 2025)
We conducted high-resolution wind-tunnel simulations to study in situ star formation in the stripped tails of two massive ( M star = 10 11 M ⊙ ) galaxies undergoing time-evolving ram pressure stripping. One galaxy was stripped face-on (W0), and the other was subject to an angled wind (W45). We find that the majority of the stars in the tail form close to the galaxy disc at the beginning of stripping. Most stars have ages that reflect outside-in stripping, as older stars are found at larger radii than younger stars. The velocities and metallicities of stars indicate that the intracluster medium mixing both increases the velocity and decreases the metallicity of star-forming gas, leading to faster lower metallicity stars at larger distances from the galaxies. However, not all stars follow this simple model, even in the case of face-on stripping. Indeed, a considerable number (15–25%) of tail stars are formed with negative velocities, indicating the fallback of star-forming gas on to the galaxy. Almost all of the tail stars formed within 20 kpc from the disc will eventually fall back on to the galaxy, and their contribution to the intracluster light is negligible. The orbits of the stars formed in the tail result in an extended (and asymmetric in the case of W45) stellar distribution around the disc. Mock UV images reveal that the observed vertical distribution of stars in a stripped galaxy is not significantly broader than in an undisturbed galaxy, indicating that more stars would need to form in the stripped tail than what we find in our simulations to observably impact the width of the UV disc in ram pressure stripped galaxies.